Pengoptimalan Pemindahan Tanah Mekanis Dengan Sistem Multi Channel Single Phase Pada Proyek Pembangunan Retail Indomaret Kalimantan Selatan - Muhammad Ihsan Marais (Lambung Mangkurat University Press, 2022)
In Indomaret Griya Permata Banjarbaru retail Development Project in South Kalimantan, there is work related to the use of heavy equipment. Among them is earthmoving work. Earthmoving consists of a series of loading and transporting equipment. This activity is needed to achieve the target of optimal earthmoving. Optimizing earthmoving is a way to achieve optimal conditions for using heavy equipment. This study discusses the optimization of dump truck queue time and the number of dump trucks. The calculation of tool performance is using the tool production capacity method. Besides that, it also analyzes the queue of heavy equipment so that it is optimal with the queuing system method. The results obtained from the calculation of the operation of the existing heavy equipment show that the queue time for dump trucks is 40 minutes, with 6 units of dump trucks queuing. Then, from the results of optimizing the number of excavators used from 2 units to 4 units, it was found that the number of dump trucks in line was less than 1 minute, and operational costs per day decreased from IDR 17,400,000,- to IDR 14,800,000,-.